2021
DOI: 10.3390/diagnostics11050737
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Baveno VI Criteria Using Liver Stiffness Measured with a 2D-Shear Wave Elastography Technique

Abstract: The present study evaluates the performance of Baveno VI criteria, using liver stiffness (LS) assessed with a 2D-SWE elastography technique, for predicting high-risk varices (HRV) in patients with compensated advanced chronic liver disease (cACLD). A secondary aim was to determine whether the use of spleen stiffness measurements (SSMs), as additional criteria, increases the performance of the 2D-SWE Baveno VI criteria. Data were collected from 208 subjects with cACLD, who underwent abdominal ultrasound, liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…A meta-analysis involving 12 studies showed that liver stiffness measured on TE was well correlated with HVPG and demonstrated a sensitivity of 91.2% and specificity of 81.3% in diagnosing clinically significant PH (cut-off values 13.6-18.6 kPa)[ 88 ]. In contrast, despite much less applied than TE, SWE also exhibited encouraging profiles in predicting PH and esophageal varices (AUC: 0.86-0.89)[ 89 - 93 ].…”
Section: Progression Of Diffuse Liver Diseasementioning
confidence: 99%
“…A meta-analysis involving 12 studies showed that liver stiffness measured on TE was well correlated with HVPG and demonstrated a sensitivity of 91.2% and specificity of 81.3% in diagnosing clinically significant PH (cut-off values 13.6-18.6 kPa)[ 88 ]. In contrast, despite much less applied than TE, SWE also exhibited encouraging profiles in predicting PH and esophageal varices (AUC: 0.86-0.89)[ 89 - 93 ].…”
Section: Progression Of Diffuse Liver Diseasementioning
confidence: 99%
“…3). The remaining 61 (67.8%) patients were continued to follow up without hypersplenism upon a median period of 22 months (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Clinical Outcome Of the Follow-upmentioning
confidence: 99%
“…The Baveno VI criteria (2015) suggests that transient elastography (TE) can clinically identify significant portal hypertension (CSPH) (1b; A) [16]. On this basis, Fofiu R raised 2D-SWE had a good performance to predict high-risk varices (HRV),) including esophageal varices (EV) and gastric varices (GV) in advanced chronic liver disease (cACLD) [17]. However, no attention has yet been paid to the value of 2D-SWE to predict hypersplenism in WD patients mainly due to the rarity of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Elasticity is illustrated as a color-coded elastogram, enabling both a qualitative and quantitative LS estimation. Several studies ascertained the usefulness of 2D-SWE in assessing the stiffness of different organs such as the liver, spleen, or thyroid [ 5 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%